In-stent restenosis and stented-territory infarction after carotid and vertebrobasilar artery stenting - Jae-Chan Ryu; Jae-Han Bae; Sang Hee Ha; Boseong Kwon; Yunsun Song; Deok Hee Lee; Jun Young Chang; Dong-Wha Kang; Sun U. Kwon; Jong S. Kim; Bum Joon Kim (BMC Neurology, 2023)
Abstract Background Prognosis after vertebrobasilar stenting (VBS) may differ from that after carotid artery stenting (CAS). Here, we directly compared the incidence and predictors of in-stent restenosis and stented-territory infarction after VBS and compared them with those of CAS. Methods We enrolled patients who underwent VBS or CAS. Clinical variables and procedure-related factors were obtained. During the 3 years of follow-up, in-stent restenosis and infarction were investigated in each group. In-stent restenosis was defined as reduction in the lumen diameter > 50% compared with that after stenting. Factors associated with the occurrence of in-stent restenosis and stented-territory infarction in VBS and CAS were compared. Results Among 417 stent insertions (93 VBS and 324 CAS), there was no statistical difference in in-stent restenosis between VBS and CAS (12.9% vs. 6.8%, P = 0.092). However, stented-territory infarction was more frequently observed in VBS than in CAS (22.6% vs. 10.8%; P = 0.006), especially a month after stent insertion. HbA1c level, clopidogrel resistance, and multiple stents in VBS and young age in CAS increased the risk of in-stent restenosis. Diabetes (3.82 [1.24–11.7]) and multiple stents (22.4 [2.4–206.4]) were associated with stented-territory infarction in VBS. However, in-stent restenosis (odds ratio: 15.1, 95% confidence interval: 3.17–72.2) was associated with stented-territory infarction in CAS. Conclusions Stented-territory infarction occurred more frequently in VBS, especially after the periprocedural period. In-stent restenosis was associated with stented-territory infarction after CAS, but not in VBS. The mechanism of stented-territory infarction after VBS may be different from that after CAS.